Serous ovarian carcinoma. Cytological and immunocytochemical and molecular genetic diagnostics - O. G. Grigoruk; E. E. Pupkova; L. M. Bazulina; A. F. Lazarev (Опухоли женской репродуктивной системы)
The results of diagnostics of 65 patients with serous ovarian carcinoma are given in the article. Analysis of the investigation has allowed to include 13 patients (20 %) in the group 1 (low grade) and 52 (80 %) in the group 2 (high grade). According to the results of the executed work it is determined that the Immunocytochemical technique allows to verify ovarian carcinoma, differentiating it with carcinoma metastases of the other organs, that is very important for following treatment. In case of sufficient tumour cells in cytological specimens, specimens are valuable material for molecular-genetic researches. According to the results of genetic DNA investigations, suitable for the estimation, there was absence mutation of V600E in the BRAF-gene in all cases. The genetic mutation of KRAS-gene with 5 patients from the group1 (low grade) was noticed. Among them the genetic mutation of G12V was detected in 4 cases and mutation of G12D in 1 case. The mutations in the BRCA1-gene weredetected in 4 cases from the 2th group (high grade) three of them were presented by 5382insC mutation and one of them by T300G mutation. The usage of the multivariate analysis evaluating the cell composition of low and high grade carcinomas was allowed to distinguish the most significant features off ovarian carcinoma cells that will be allow to differentiate them by means of light microscopy.